2015
DOI: 10.1007/s00701-015-2519-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of craniopharyngioma with special reference to autocrine/paracrine signaling: underestimated implication of growth hormone receptor

Abstract: High expression of GHR is associated with shorter duration of postoperative stable disease in patients with craniopharyngioma. If the surgical specimens were craniopharyngiomas with high GHR expression, GH supplementation would be introduced quite prudently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…4,47,50,51 GH accelerates tumor progression through autocrine/paracrine effects on cancer cell behavior and neighboring cells within the tumor microenvironment. These effects include promoting cell survival/proliferation, 52,53 migration/invasion, 53,54 oncogenic transformation, 55,56 and epithelial-to-mesenchymal transition, 54,57,58 as well as promoting tumor angiogenesis 59 and lymphangiogenesis 60 and enhancing a cancer stem cell-like phenotype. 57,61 These effects have been observed in multiple tumor types, including breast, endometrial, and hepatocellular carcinomas, and lung cancer, melanoma, prostate cancer, and colon cancer.…”
Section: Gh Excess: Disease Indicationsmentioning
confidence: 99%
“…4,47,50,51 GH accelerates tumor progression through autocrine/paracrine effects on cancer cell behavior and neighboring cells within the tumor microenvironment. These effects include promoting cell survival/proliferation, 52,53 migration/invasion, 53,54 oncogenic transformation, 55,56 and epithelial-to-mesenchymal transition, 54,57,58 as well as promoting tumor angiogenesis 59 and lymphangiogenesis 60 and enhancing a cancer stem cell-like phenotype. 57,61 These effects have been observed in multiple tumor types, including breast, endometrial, and hepatocellular carcinomas, and lung cancer, melanoma, prostate cancer, and colon cancer.…”
Section: Gh Excess: Disease Indicationsmentioning
confidence: 99%
“…identified 10 hub genes for potential application in early diagnosis and therapy for ACP. Several studies have also identified the associations between the prognosis of CP and many biomarkers, including B7-H3 [ 51 ], β-catenin [ 52 ], and growth hormone receptors [ 53 ]. Moreover, another study identified four inflammatory mediators (CXCL6, CXCL10, CXCL11, and CXCL13) as hub genes with great value for targeted therapy in CP [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Where possible a histological diagnosis should be obtained prior to definitive treatment, unless appearances are clearly typical intraoperatively or in neurosurgical emergencies. No molecular markers correlate with overall (OS) or progression-free survival (PFS) and therefore need not be measured routinely [37][38][39][40][41] .…”
Section: Be Aware That Ki67 Labelling or Ctnnb1 Mutation Analysis Of ...mentioning
confidence: 99%